Russia in Africa: Is great power competition returning to the continent? - Agnieszka Paczyńska (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Since 2014, Russian involvement in Africa has grown significantly. African leaders have been receptive to these overtures as a result of increasing concerns about growing Chinese dominance, retrenchment of the United States (US) and their interest in diversifying trading and security partners. Russia cultivates these relationships by relying on the legacy of the Soviet Union's support for anti-colonial and liberation movements, and focuses on strengthening diplomatic, military and economic collaborations. This analysis shows that: * Overall, Russia's strategy in Africa appears to involve a mix of arms sales, political support to authoritarian leaders and security collaborations - in exchange for mining rights, business opportunities and diplomatic support for Russia's foreign policy preferences. The offers of military assistance and political support, especially for authoritarian leaders, have opened doors to Russian firms and strengthened diplomatic relationships. The support of African allies has been especially important to Russia at the United Nations (UN), where African countries account for a quarter of all votes in the General Assembly. * Russian trade and investment in Africa has grown significantly, particularly in north Africa. Yet, Russia remains a minor economic player on the continent in comparison to China, India or the US. Russia's support for smaller states, especially those that have been internationally shunned, gives Moscow significant influence in those countries. * As of autumn 2019, Russia had concluded military cooperation agreements with 21 African countries and is negotiating the establishment of military bases in a number of states. It is also providing counter-terrorism training. Russia is currently the largest supplier of arms to the continent. * Russia is increasing efforts to influence elections. Its strategy focuses on shoring up authoritarian strongmen in unstable yet resource-rich states thus bolstering these regimes' ability to persist. These priorities are in stark contrast to popular opinion on the continent, which favours democracy. * Russia remains a relatively minor economic and political player on the continent, and European Union (EU) and US concerns that Russian expansion in Africa draws the continent into a broader geopolitical struggle between great powers are overstated. * Germany and the EU should counter Russian assistance to authoritarian leaders by bolstering support for good governance and civil society strengthening initiatives.
Keywords: 330